Book Review: Mismatch - Melvyn L. Fein (Journal of Public and Professional Sociology)
Review of the book MisMatch: How Affirmative Action Hurts Students It’s Intended to Help, and Why Universities Won’t Admit It, by Richard H. Sander and Stuart Taylor, Jr.